Oral health in young elite swimmers - Cardoso, F.; Monteiro, A. S.; Fernandes, A.; Vilas-Boas, J. P.; Pinho, J. C.; Pyne, D. B.; Fernandes, R. J. (Trends in Sport Sciences, 2020)
Evidence of a lack in oral healthcare in sport has emerged since reports from Olympic Games indicated a higher risk for problems of the oral cavity. Oral diseases could affect well-being and the quality of life, with anecdotal reports that athletes are concerned about their oral conditions and potential impairment of performance. Aim of Study. Our purpose was to observe, through a clinical perspective, the orofacial development, dental relationships and oral health of young elite swimmers. Material and Methods. A cohort of 17 young elite swimmers were evaluated for skeletal and occlusion development or problems arising from gums and teeth. Results. Several conditions (e.g. pattern II, class III and crossbite) differed from the normal skeletal and dental development but most of the swimmers evaluated had a proper position of bone bases and teeth. Dental caries (n = 5) and gum-inflammatory states (n = 3) were also detected. Conclusions. Oral health status was not completely monitored in our group of elite swimmers. Strategies to prevent oral diseases and promote oral health within sport need to be developed. Good oral health practices should be a priority for athletes, clubs and sports federations.